Benzoin Business Opportunity Analysis in Conservation Areas: Case Study of Bukit Tiga Puluh National Park - Ayu, Sari; Zuhud, Ervizal AM; Bahruni, Bahruni (Fakultas Kehutanan Universitas Mulawarman, 2025)
This study analyzes the business potential and commercial benefits of benzoin (Styrax benzoin) in the Bukit Tigapuluh National Park (TNBT) conservation area, while exploring the traditional ecological knowledge of the Talang Mamak community in forest resource management. Benzoin is a non-timber forest product with high economic value used in cosmetics, pharmaceuticals, and perfumery. This research employed a descriptive qualitative method through ethnobioprospecting and supply chain analysis. The findings show that despite its high market value, farmers earn minimal profits due to reliance on middlemen and limited access to markets and processing technology. The study recommends strengthening farmers’ capacity through training, product diversification, and community-based marketing support. A benzoin conservation strategy should actively involve local communities as key actors in sustainable forest management.